Emerging models and paradigms for stem cell ageing - Jones, D. Leanne (2011)
Ageing is accompanied by a progressive decline in stem cell function, resulting in less effective tissue homeostasis and repair. Here we discuss emerging invertebrate models that provide insights into molecular pathways of age-related stem cell dysfunction in mammals, and we present various paradigms of how stem cell functionality changes with age, including impaired self-renewal and aberrant differentiation potential.